Collective Management in a Cooperative: Problematizing Productivity and Power - (:unkn) unknown (My University, 2016)
Since the mid-twentieth century, the structure of the workplace has undergone a transformation. While the conventional firm with its rigid bureaucracies is still in use, many businesses have grown increasingly flexible, flat, and polycentric: “empowerment” and “innovation” are the coin of the realm. As the way we work changed, professional communication scholarship pivoted to consider communication practices in these structures. While professional communication scholars have long discussed these kinds of organizations, they have not discussed an increasingly popular alternative: cooperatives. Owned and operated by the people who use them, these organizations can significantly affect the communities in which they operate. To contribute to the rhetorical knowledge of cooperatives, I conducted a qualitative study at the Riverwest Public House Cooperative (“Public House”). This project extends research of flat organizations by investigating a cooperative business. I draw my research questions from the concerns scholars identified in other kinds of organizations: namely, the role of genres in configuring power and facilitating organizational change (Clark 2006; Devitt 1991; Spinuzzi 2007; Star 1991; Winsor 2003; Zachry 2000). 1. How does a cooperative employ genres differently? 2. What do these texts tell us about how power is distributed in a cooperative? 3. How do the genres it employs affect organizational change? These questions helped me better understand the connections between negotiations of power and texts at work in this particular business, leading me to several findings: 1. Genres. Collaboratively produced texts are the backbone of consensus-based decision-making. Unlike conventional organizations, in a cooperative, many (though not all) stakeholders are given access to governance. For instance, documents like an incident report or safer space policy have greater social significance when they are not only produced by agreement but also enforced through agreement. 2. Organizational Change. The Public House underwent a managerial overhaul during my study. Like conventional businesses, change occurred through a confluence of material circumstances and individual and organizational goals; however, due to the absence of formal structure, in this instance, a broader range of individuals was able to institute structural change. 3. Distribution of Power. In place of hierarchy, rhetorics of empowerment and democracy were deployed horizontally to task employees with managerial duties without financial rewards. For this project, I provide an interdisciplinary take on hierarchy and organizational structure by examining one cooperative, still in its infancy, through the lens of genre and power in the workplace.
Keywords: Actor-network Theory; Cooperative; Empowerment; Hierarchy; Horizontal; Rhetoric